The Influence of Asset Expansion and Revenue Growth on Capital Structure - Mahmudah, Ayu Anis; Suntari, Esti (IJESS International Journal of Education and Social Science, 2025)
This scholarly investigation sought to ascertain the influence of asset augmentation and sales expansion on the financial architecture of PT Mayora Indah Tbk, spanning the fiscal years 2014 through 2024. A quantitative descriptive methodology was employed, leveraging multivariate linear regression analysis. The foundational data were extracted from the enterprise's officially published annual financial statements. The statistical t-test indicated that Asset Expansion did not exert a statistically significant effect on capital structure, as evidenced by a t-statistic of -0.633 (which was below the critical t-value of 1.895) and an associated significance level of 0.544 (exceeding 0.05). Concurrently, Revenue Growth similarly demonstrated no discernible significant impact, with a t-statistic of 1.611 and a significance level of 0.146. The concurrent F-test corroborated these findings, revealing that both independent variables, when considered in concert, did not collectively possess a significant influence on capital structure (F-statistic of 1.299, which was less than the critical F-value of 4.74; significance level of 0.325). An Adjusted R-squared value of 0.056 implied that merely 5.6% of the variability observed in capital structure could be elucidated by the proposed model, with the substantial remainder attributable to unexamined exogenous variables.